Treatment and related morbidity of nasal cavity and paranasal sinus cancers - Smaadahl, Nils; Hool, Sara-Lynn; Reinhardt, Philipp; Mose, Lucas; Hohenberger, Ralph; Giger, Roland; Schanne, Daniel Hendrik; Anschuetz, Lukas (Frontiers in Oncology, 2024)
IntroductionSinonasal malignancies are rare and histologically heterogeneous cancers of the nasal cavity and sinuses. The treatment of choice is usually surgery and, if necessary, adjuvant radiotherapy. In this study, we aimed to investigate treatment modalities and associated morbidity.MethodsA consecutive case series of solid sinonasal cancer treated at our tertiary referral center was analyzed. We performed a retrospective chart review and statistical analysis.ResultsA total of 156 patients with sinonasal cancer were enrolled in the present study. Male patients were more frequently affected (62%) and the median age was 64 years. Squamous cell carcinoma, adenocarcinoma and malignant melanoma (MM) were the most common histopathological entities. Surgery was the primary treatment modality for 73% of curatively treated patients. Primary radiotherapy alone or in combination with systemic treatment was less frequent. Median overall (OS) and recurrence-free survival (RFS) was 164 months and 71.3 months, respectively. Multivariate analysis revealed negative associations of histology (MM) and skull base involvement on RFS and age, skull base involvement and the type of primary therapy (radiochemotherapy) on OS. Postoperative 30-day morbidity was low, with most patients (84%) experiencing no reported events. Radiotherapy was generally well-tolerated, despite most of patients experienced acute toxicity such as dermatitis (80.6%) or mucositis (72.1%). However, only one event of acute toxicity > grade 3 was reported. Long term morbidity was most frequently reported as pain (23%), dry mucosa (19%) and anosmia (14%).ConclusionWe observed negative associations of histology (MM) and skull base involvement on RFS and age, skull base involvement and the type of primary therapy (radiochemotherapy) on OS. Acute treatment-related morbidity was generally low for surgical patients and considerable for irradiated patients. Moreover, a consistent part of the cohort displayed long term morbidity.